Tuberculosis in the street population: a systematic review - Paula Hino; Thais Tiemi Yamamoto; Shyrlaine Honda Bastos; Aline Ale Beraldo; Tânia Maria Ribeiro Monteiro de Figueiredo; Maria Rita Bertolozzi (SciELO, 2021)
ABSTRACT Objective: To analyze evidence of the occurrence of tuberculosis in people living on the streets provided by the literature. Method: Systematic review conducted in the databases PubMed, EMBASE, LILACS, and SciELO electronic library. Analysis of the empirical material was guided by Hermeneutics. The main themes which give shape to the association between tuberculosis and street population were sought to be understood. Results: Initially, 343 articles were identified, but only seven met the eligibility criteria. The literature shows that homeless people with tuberculosis presented unfavorable treatment outcomes when compared to the population with fixed residence. Some of the associated reasons were abusive consumption of alcohol and other drugs and associated diseases, such as human immunodeficiency virus and others. Conclusion: Despite the importance of this theme, analysis of the scientific production has provided evidence of the need for studies aimed not only at comprehending the occurrence of disease in this vulnerable group, but specially ways of fighting it.